Bone Morphogenetic Protein-1 and Its Regulation - A Review - Niha Naveed1 , Kishorekumar S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Bone morphogenetic protein 1, also referred to as BMP1, is a protein encoded by the BMP1 gene in humans.There are seven protein isoforms created through alternative splicing.It leaves the C-terminal propeptidesof procollagen I, II and III. It induces cartilage and bone formation. It may participate in dorsoventralpatterning during early development by cleaving chordin (CHRD). It is also responsible for the proteolyticactivation of lysyl oxidase LOX.